2007
DOI: 10.1021/np0680580
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Steroidal Alkaloid Oligoglycosides, Robeneosides A and B, and Antidiabetogenic Constituents from the Brazilian Medicinal Plant Solanum lycocarpum

Abstract: In the course of our studies on antidiabetogenic compounds from natural medicines and medicinal foodstuffs, a methanolic extract of the fruits of Solanum lycocarpum showed an inhibitory effect on the increase of serum glucose levels in oral sucrose-loaded rats. Through bioassay-guided separation, three known steroidal alkaloid oligoglycosides, solamargine (1), solasonine (3), and 12-hydroxysolasonine (5), were isolated from the active fraction together with two new steroidal alkaloid oligoglycosides, robeneosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 23 publications
4
47
0
4
Order By: Relevance
“…1,3) In the course of our characterization studies of traditional Brazilian medicines, [4][5][6][7] we systematically investigated the chemical constituents of the methanolic extract from the aerial parts of C. sicyoides, which resulted in the isolation of three new flavonoid glycosides, cissosides I (1), II (2), and III (3), and the new benzofuran-type stilbene cissusin (4), together with 39 known constituents. This paper deals with the isolation and structural elucidation of four new constituents (1)(2)(3)(4), and the inhibitory effects of both the extracts and isolated compounds on the release of b-hexosaminidase from RBL-2H3 cells.…”
mentioning
confidence: 99%
“…1,3) In the course of our characterization studies of traditional Brazilian medicines, [4][5][6][7] we systematically investigated the chemical constituents of the methanolic extract from the aerial parts of C. sicyoides, which resulted in the isolation of three new flavonoid glycosides, cissosides I (1), II (2), and III (3), and the new benzofuran-type stilbene cissusin (4), together with 39 known constituents. This paper deals with the isolation and structural elucidation of four new constituents (1)(2)(3)(4), and the inhibitory effects of both the extracts and isolated compounds on the release of b-hexosaminidase from RBL-2H3 cells.…”
mentioning
confidence: 99%
“…Steroidal alkaloids, such as solamargine induces apoptosis (Shiu et al, 2009) and also solanine induced apoptosis in HepG(2) cells (Ji et al, 2008). Solamargine and solasonine, exhibited an inhibitory effect on serum glucose levels in oral sucrose-loaded rats, and this effect could be relevant for the prevention and treatment of diabetes (Yoshikawa et al, 2007). α-Chaconine, α-solanine, and α-tomatine inhibited normal human liver HeLa (Chang) cells (Lee et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that certain alkaloids induce hypoglycaemia via inhibition of intestinal glucose uptake by inhibiting α-glucosidase activities (Yoshikawa et al, 2002;Fattorusso and Taglialatela-Scafati, 2007). In addition, it has been reported that medicinal plants rich in alkaloids usually exhibit hypoglycaemic activities (Svoboda et al, 1964;Yoshikawa et al, 2007;Okonta and Aguwa, 2007;Fuji et al, 2009). Thus, result of this study suggests that HU Af could be mediating its oral hypoglycaemic effect through this mechanism, although other major phytocomponents in HU b could be mediating their hypoglycaemic effects via other mechanisms.…”
Section: Evaluation Of the Antihyperglycaemic Effect Of Hu Fractions mentioning
confidence: 99%